Limitations of dual x-ray absorptiometry in children with chronic kidney disease - Weber, Lutz T.; Mehls, Otto (Pediatric nephrology, 2010)
Dual x-ray absorptiometry (DXA) is the most widely used densitometric method for diagnosing osteoporosis in adults. It has also been widely adopted as a diagnostic tool in the pediatric population. The most significant limitation of DXA is its reliance on areal rather than volumetric bone mineral density (BMD), which results in an artificial underestimation of bone density in short people. Poor longitudinal growth, however, is an eminent problem in children with chronic kidney disease (CKD). There is also no evidence in children that areal BMD is predictive of future fracture risk, which is the traditional rationale for measuring BMD in children with CKD. Therefore, the Kidney Disease Outcomes Quality Initiative guidelines and the current position of the International Society for Clinical Densitometry (ISCD) on pediatric patients, both of which are presented in this issue of Pediatric Nephrology, do not recommend the use of DXA in children with CKD. To date, there is no consensus on the best method to assess the degree of renal osteodystrophy in this patient population, and further collaborative efforts to correlate densitometric findings with clinical outcomes are warranted.
Online veröffentlicht am 15. Juli 2009
Gesehen am 17.10.2023